Periodyczne Drgania Swobodne Belki przy Słabo-Nieliniowych Warunkach Brzegowych - Szemplińska-Stupnicka, W. (Engineering Transactions, 1967)
Natural periodic vibration of a homogeneous beam is considered in the case of the presence of small nonlinear terms in two boundary conditions. In the first approximation periodic solution is obtained by means of the modified perturbation method. It is shown that the correction coefficients of natural frequencies and modes are, for two nonlinear boundary conditions, sums of the corresponding coefficients for a single nonlinear condition. It is also shown that the principle of superposition remains valid for a larger number of nonlinear conditions.